(untitled) (MIST International Journal of Science and Technology, 2023)
The growing necessity of large aperture-based structures for many aerospace applications emphasizes the need to deploy large antenna structures in space. The space antennas should be light in weight and have low stowage volume, with efficient membrane packaging. The concept of additive manufacturing has been introduced to reduce weight as well as cost. In this paper, a comparative study has been done to analyze the advancement made in reducing weight with adequate strength. Based on the study, the main objectives are to develop a 3D-printed spherical reflector model with high specific strength and to assess the consistency of the model’s shape. For determining the specific strength, tensile testing is performed on four different infill densities (20%, 40%, 60%, and 80%) with a grid infill pattern. It was observed that the specimen with 80% infill density has the highest tensile strength, 36.56 MPa, which is 23.51% more than 20% infill. However, the specimen with 20% infill density has the highest specific strength of 19.323 GPa/kg among the four specimens, which is approximately 64.64% higher than the 100% infill density. As a result of the testing, the spherical reflector model is 3D printed with 20% infill density, and it was found that the model achieves its shape stability and shape consistency with adequate specific strength. MIJST, Vol. 11, December 2023 : 43-51 DOI: https://doi.org/10.47981/j.mijst.11(02)2023.431(43-51)